Genetic Mapping and QTL Analysis of Stigma Color in Melon (Cucumis melo L.) - Lv, Yuanzuo; Gao, Peng; Liu, Shi; Fang, Xufeng; Zhang, Taifeng; Liu, Tai; Amanullah, Sikandar; Wang, Xinying; Luan, Feishi (Frontiers in Plant Science, 2022)
Melon is an important Cucurbitaceae crop. Field observations had shown that the green stigmas of melon are more attractive to pollinators than yellow stigmas. In this study, F2 and F2:3 populations obtained by crossing MR-1 (green stigma) and M4-7 (yellow stigma) were used for genetic analysis and mapping. A genetic map of 1,802.49 cm was constructed with 116 cleaved amplified polymorphism sequence (CAPS) markers. Two stable quantitative trait loci (QTLs) linked to the trait of stigma color were identified on chromosomes 2 (SC2.1) and 8 (SC8.1), respectively. An expanded F2 population was used to narrow down the confidence regions of SC2.1 and SC8.1. As a result, SC2.1 was further mapped to a 3.6 cm region between CAPS markers S2M3 and S2B1-3, explaining 9.40% phenotypic variation. SC8.1 was mapped to a 3.7-cm region between CAPS markers S8E7 and S8H-1, explaining 25.92% phenotypic variation. This study broadens our understanding of the mechanisms of stigma color regulation and will be of benefit to the breeding of melon.